Startups: riscos e responsabilidade do investidor-anjo no Brasil - Maia, Torben Fernandes (2019)
The present dissertation is a project that emerged from the perspective of a global phenomenon that begins to replicate itself in Brazil: a deep, intense and a perspective of social and social panoramas, promoted by the emergence of new technologies, provided by a new way to undertake, which is the startups companies. The global climate, present in this niche market, is increasing, investors, the state and society. Recognizing the importance of the new panorama and its impact on legal relations, economy and society, the present work had an analysis on the global context, the revolution, its impacts and the development of startups systems in Brazil, discussed the ways in which angel investment is contracted, which is an outstanding financing modality in the segment, due to the intelligent money that accompanies it and the ability to mitigate the risks and uncertainties, inherent and more pronounced characteristics of the companies and later risks and limits of civil liability were legally established. Thus, initially, an analysis of entrepreneurship in Brazil is made and how transformations are taking place. Following on, narrowing the discussions, the leading startups, are the most widely used forms of financing and ways to contract investments. And in the end the central focus point on the risks that can be faced by the angels investing in startups, where through analysis of the applicable legislation for the selected operational model and judged select of the country courts on how a matter of disregard of is subject to be faced, due to legal, consumer, labor and tax relations. Thus, a social contribution is a study about the ability to collaborate with the development of the Brazilian startups ecosystem, insofar as a legal analysis of important formal aspects of an instrument that it occupies is given to an academic, economic and collective community. a space of expression in this peculiar market, which is that of investments, capable of materializing as disruptive of ideas.